The Effect Of Cash Ratio And Receivable Turnover On Net Profit Margin - Heru Prayitno, Yogo (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to make sure the effect of cash ratio & receivable turnover on net profit margins. This research is motivated by an increase in the efficiency and effectiveness of the corporate in running the company. To measure the efficiency of corporate activities, one of them is the ability to obtain profits that are measured using profitability ratios. Net profit margin is used to calculate the capacity of a corporation with all reserves put into assets used for the corporation’s operations to gain revenue. Cash ratio’s calculate a corporation’s capacity to pay short-term debt. Receivable turnover provides an understanding of the company’s quality and the company’s success in collecting these receivables. The population of this research’s corporations are in the sector of industry of consumer goods listed on the ISX for the period of 2016-2018, namely 52 companies. The sampling technique uses purposive sampling so that there are 35 companies that meet the criteria. The outcomes of the research stated that partially the cash ratio affected the net profit margin, receivable turnover affected the net profit margin, and simultaneously the cash ratio and receivable turnover affected the net profit margin.